Transverse strength of railway tracks: part 3. Multiple scenarios test field (Fracture and Structural Integrity, 2014)
In the present paper the design and construction choices of a test field for the ballast lateral resistance measurement, in order to produce data useful for the development of a numerical model able to simulate the service critical conditions of a continuous welded rail track, are described. Some construction details described herein allow to better understand the methodological approach followed in the design of experiments, the tests management philosophy as well as of the accuracy achieved in their implementation.
Keywords: Test field.